The Effect of Knowledge Management through Human Resources Information Systems on Customer Relationship Management in Aquatic Sport Centers - Mohammad Keshtidar; Mohamad Reza Esmaeilzade Ghandehari; Mohsen Harati (The Society of Aging and Physical Activity (SAPA), 2017)
Objectives. The purpose of this research is to investigate the impact of knowledge management through information systems of human resources on customer relationship management. Methods. The study population included managers and employees of Mashhad's aquatic sport centres like 'Blue Waves', 'Armaghan', 'Surging Waves', and 'Sunshine Coast Park' (600 persons). Using a Morgan table, 234 cases were selected as sample, based on cluster sampling method, and randomly. The research method was descriptive-analytical. Data collection was conducted as a field study. The measurement tools were knowledge management questionnaire and human resources information systems questionnaire  and customer relationship management questionnaire respectively. The validity of the questionnaires was observed andapproved by 10 sports management experts and professors of Azad University of Mashhad and Ferdowsi University of Mashhad.Validation was determined by Cronbach's alpha respectively as 0.91, 0.87 and 0.90. Results. The results showed that knowledge management through human resources information systems has a significant positive effect on customer relationship management. Conclusion. It can be said that aquatic sport centers should more attend the important role of information systems to increase customer satisfaction along with knowledge management.